The relationship between English language and History performance at 'O' level in some selected Kampala secondary schools - Babirye, Mary Kakeeto (Kampala: Makerere University, 1993)
Thesis (M. Educ.) - Makerere University, 1993.
Includes bibliographical references (p. 50-58)
Keywords: English language -- Study and teaching -- Uganda; History -- Study and teaching -- Kampala District -- Uganda